Pengaruh Gamification Terhadap Purchase Decision Melalui Customer Experience Dan Customer Brand Engagement - Kudadiri, Diana Rose; Astuti, Sri Rahayu Tri (Faculty of Economics and Business | Universitas Diponegoro, 2024)
The purchasing behaviors of consumers are profoundly influenced by the widespread availability of digital technologies and internet connectivity. In pursuit of exceptional products and services, consumers are increasingly prioritizing favorable and memorable experiences. Consequently, enterprises must acknowledge the criticality of fostering enduring relationships with customers in order to sustain their brand recognition and attract new clientele by means of personalized customer experiences. One commonly utilized tactic by retailers to heighten consumer engagement and purchase frequency is the integration of gamification. An instance of such implementation can be observed in the e-retail domain in Indonesia, where Alfamart leverages the concept of gamification through its Alfagift platform for online shopping. This research endeavors to assess the impact of gamification on consumer purchase decisions within the realm of Alfagift, with customer experience and customer brand engagement discerned as intervening factors. The study encompasses a population comprising consumers or users of Alfagift who have completed transactions via the application, with a sample size of 102 individuals selected through purposive sampling. The data underwent analysis via structural equation modelling (SEM) utilizing the SmartPLS 4.0 software. Findings indicate that gamification exerts a beneficial influence on customer experience and customer brand engagement, subsequently affecting consumer purchasing decisions. Further, it is established that customer experience and customer brand engagement serve as mediators in the relationship between gamification and consumer purchasing decisions within Semarang City. Notably, customer brand engagement emerges as the foremost influential variable, succeeded by gamification, customer experience, and purchase decision.